Bilateral seminal vesicle calculi: A case report (Indian Journal of Case Reports, 2020)
Seminal vesicle calculi are rare and so usually remain undiagnosed. Most of the patients with seminal vesicle calculus present with hematospermia, ejaculatory pain, perineal or testicular pain, or low volume of ejaculate. Hematospermia is the most common symptom present in 70% of the cases. Patients may have ejaculatory ductal obstruction secondary to bilateral seminal vesicle calculi and may present with impaired fertility and azoospermia. We present the case of a 41-year-old male who presented with ejaculatory pain of 6 months duration. On evaluation with ultrasonography and magnetic resonance imaging, a diagnosis of bilateral seminal vesicle calculi was made. The patient underwent bilateral transutricular seminal vesiculoscopy with laser lithotripsy.